Stubborn fat gone!# ebook - Cruise, Jorge (2015)
Most likely the fat that bothers you most is belly fat. Despite exercising and eating a diet low in Sugar Calories, you’re still stuck with that stubborn fat. So what’s the missing link? Breakthrough research has confirmed that combining the right diet with the right mind-set is the secret to eliminating the most stubborn of all fat – belly fat. Stress is the number one reason so many of are led to self-sabotage when trying to eat well, but following Jorge Cruise’s revolutionary Carb Control™ will curb your cravings and balance your hormones. Let Jorge guide you with daily planners full of easy, toss-together meals, and you can lose up to 11 lbs. in your first week alone!